Comportamiento clínico epidemiológico del carcinoma escamocelular bucal de pacientes tratados en el hospital Universitario San Vicente de Paúl (HUSVP), Medellín, entre enero de 1990 y diciembre de 1996 (2005)
ABSTRACT: Oral squamous cell carcinoma is a pathology that has a very low frequency in the Stomatology Service. The purpose of this article is to describe the clinical and epidemiological characteristics of the cases diagnosed in the HUSVP for the years of 1990 to 1996. Clinical records and files from the department of Pathology of the Hospital and of the School of Dentistry were analyzed. 228 cases were found, of them, the largest percentage corresponded to men of 60 years of age or older. The most affected site was the tongue (30%), followed by the floor of the mouth (20.7%) and the palate (17.7%).Smoking was reported by 67% of the patients, and alcohol consumption by 29.8%. A pre malignant lesion previous to the appearance of the cancer was detected in 56 cases, of these, leukoplakia was the most common. The most common stages of cancer detected were stage IV and III with 55.1% and 19.8% respectively; radio therapy in 46.1% of the cases and surgeries in the 39.6% of the cases were the most performed treatments. It is concluded that in the population studied, the oral squamous cell carcinoma is diagnosed mainly in older people and in advanced stages, this decreases the possibility of curative treatments and at the same time affects negatively the quality of life of patients; it is necessary to understand the clinical behavior, , the manifestations, the characteristics of the initial stages and the possible associated risk factors in order to make an early diagnosis and control of this neoplastic disease.